Self-determination trajectories at work: A growth mixture analysis - Fernet, C.; Morin, A.J.S.; Austin, S.; Gagné, Marylène; Litalien, D.; Lavoie-Tremblay, M.; Forest, J. (ACADEMIC PRESS INC ELSEVIER SCIENCE, 2020)
© 2020 Elsevier Inc.